A Literature Review: Strategy Design of Transition Space Using Wind Potential - Andyka Dwi Acsazha; I Gusti Ngurah Antaryama; Vincentius Totok Noerwasito (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2019)
Transition space is a link between one space and another space where this space has a function of adaptation to changing conditions from the previous space to the next space, this study discusses some transition space design strategies in building skyscrapers and groundscrapers by utilizing wind potential through usable design building elements. By implementing a transitional space strategy in building skyscrapers or groundscrapers where buildings can adapt energy-efficient buildings. Energy savings can be applied through available natural elements, one of which is wind potential. This research phase requires literature review and transitional space theory to translate the role of transition space in buildings to achieve energy-efficient buildings by utilizing wind. The case study will provide a direct example of the building of transitional space functions to anticipate the wind. The results of this study will provide a transitional space design strategy through architectural passive elements that respond to wind so as to provide comfort for building users using natural ventilation so that energy use is more efficient.